Images of Strategy - David Wilson; Stephen Cummings (UK Blackwell Publishing, 2003)
Images of Strategy develops an innovative and multi-faceted approach to strategic management which will enable students to use and develop interesting and wide-ranging applications alongside some of the latest ideas and analysis. An innovative and multi-functional approach to strategic management. Approaches strategy from different viewpoints: functional, eg technology and systems management, marketing, accounting and HRM, and analytical, eg organization theory, game theory and knowledge management Helps students to analyse, integrate and apply the many competing functional elements of strategic choice in today's world. Includes case examples to illustrate the chapters. Provides further reading sections and student questions Written by a team of top management scholars with many years of successful MBA teaching experience.